The Discourse on Counter-Narratives to Extremism in The Qur’an: A Study of Tafsīr al-Fātiḥah by Abu Nur Jazuli Amaith - Hanik Rosyida; Mohammad Abdul Aziz; Asfaq Danial; Yusuph Dauda Gambari (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2024)
The popular interpretation of Qs. al-Fātiḥah [1]: 6-7 is that al-maghḍūb and al-ḍāllīn refer to Jews and Christians. In the extremist view, this interpretation is used to justify jihād against perceived enemies of Islam. This study, using the content analysis method, explores the counter-narrative to extremism in Tafsīr al-Fātiḥah by Abu Nur Jazuli Amaith. The primary source of this study is Jazuli’s Tafsīr al-Fātiḥah. The results of this study are twofold: Firstly, the main idea of Qs. al-Fātiḥah is that guidance is God’s prerogative. Therefore, it is wrong to be intolerant and fanatical towards other religious communities simply because they do not align with Islamic values and teachings. Secondly, the counter-narrative to extremism in Tafsīr al-Fātiḥah is an effort to reframe the understanding that those who are astray and incur wrath are not only Jews and Christians, but also Muslims who deviate from truth and act extremely. These findings contribute to the understanding that Islam does not belittle other religious communities but criticizes their acts and traits. This idea can encourage Muslims to be more moderate and tolerant towards outsiders while remaining critical of insiders.